PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO DISERTAI LKS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA NEGERI 1 PASAMAN - Nofitri, Yulia; Febriana, Rina; sovia, Anny (Pendidikan Matematika, 2014)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  ABSTRACTThe research was based on students matematic concept comprehension still low of XI IPA Â grade students of SMA Negeri 1 Pasaman. The purpose of this research is to find which one is better between the using in âBisnis Berisikoâ Technique with studentâs work sheet compared with conventional learning in studentâs understanding of learning mathematics. This is the kind of experiment research, with the subject random. The population of this research is all of XI IPA grade students SMA Negeri 1 Pasaman that consists of and clasres. The sample is taken randomly and XI IPA.3 as a experiment class and XI IPA.4 as a control class. The instrument of this research is the find test with indicator consept understanding and sclaring based on analytic ârubricâ. The form of test is a essay concept with reliable test Â is 0,78. The analysis data used is the test of t with MINITAB software. Based of result in analysis data found that two sample classes are distributed normally and having the homogeny variation in a level 95%. The hypothesis testing find P-value = 0,023 and itâs smaller than at Â = 0,05. So, itâs can concluded that the studentâs concepts understanding by using âBisnis Berisikoâ technique is better than the conventional learning in XI IPA grade students of SMA Negeri 1 Pasaman.